Biofeedback interventions for individuals with cerebral palsy: a systematic review. Issue 20 (25th September 2019) - MacIntosh, Alexander; Lam, Emily; Vigneron, Vincent; Vignais, Nicolas; Biddiss, Elaine
Abstract: Purpose: The purpose of this study is to evaluate the quality of evidence of biofeedback interventions aimed at improving motor activities in people with Cerebral Palsy (CP). Second, to describe the relationship between intervention outcomes and biofeedback characteristics. Methods: Eight databases were searched for rehabilitation interventions that provided external feedback and addressed motor activities. Two reviewers independently assessed and extracted data. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework was used to evaluate quality of evidence for outcome measures related to two International Classification of Functioning, Disability and Health (ICF) chapters. Results: Fifty-seven studies were included. There were 53 measures related Activities and Participation and 39 measures related to Body Functions. Strength of evidence was "Positive, Very-Low" due to the high proportion of non-controlled studies and heterogeneity of measures. Overall, 79% of studies and 63% of measures showed improvement post-intervention. Counter to motor learning theory recommendations, most studies provided feedback consistently and concurrently throughout the intervention regardless of the individual's desire or progress. Conclusion: Heterogeneous interventions and poor study design limit the strength of biofeedback evidence. A thoughtful biofeedback paradigm and standardized outcome toolbox can strengthen the confidence in the effect of biofeedback interventions for improving motor rehabilitation for people with CP. Implications for Rehabilitation: Biofeedback can improve motor outcomes for people with Cerebral Palsy. If given too frequently, biofeedback may prevent the client from learning autonomously. Use consistent and concurrent feedback to improve simple/specific motor activities. Use terminal feedback and client-directed feedback to improve more complex/general motor activities.